2017
DOI: 10.3389/fphys.2017.00935
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of NOX4 in the Failing Human Heart

Abstract: Increased oxidative stress is a major contributor to the development and progression of heart failure, however, our knowledge on the role of the distinct NADPH oxidase (NOX) isoenzymes, especially on NOX4 is controversial. Therefore, we aimed to characterize NOX4 expression in human samples from healthy and failing hearts. Explanted human heart samples (left and right ventricular, and septal regions) were obtained from patients suffering from heart failure of ischemic or dilated origin. Control samples were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 53 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…Consistent with a role of Nox4 in senescence and oxidative stress in the cardiovascular system, increased expression of Nox4 and novel short isoforms of this oxidase were found in samples of failing hearts of human patients [ 111 ]. It is unknown, however, whether these novel isoforms are functional, and the type of ROS they can produce.…”
Section: Nox4 In Senescencementioning
confidence: 68%
“…Consistent with a role of Nox4 in senescence and oxidative stress in the cardiovascular system, increased expression of Nox4 and novel short isoforms of this oxidase were found in samples of failing hearts of human patients [ 111 ]. It is unknown, however, whether these novel isoforms are functional, and the type of ROS they can produce.…”
Section: Nox4 In Senescencementioning
confidence: 68%
“…While NOX2 causes cardiac hypertrophy through angiotensin II, NOX4, which partially localizes to the mitochondria, is associated with cardiac hypertrophy due to increased pressure overload from myocardial stresses in the failing human heart. While NOX4 is found to increase myocardial angiogenesis and protect against contractile dysfunction in HF 42 , recent evidence suggests that NOX4 in failing heart models undergoes alternative splicing, which may explain its detrimental involvement in HF 47 . Other studies have shown that NOX4 depletion decreased mitochondrial swelling and cytochrome c release and decreased mitochondrial DNA (mtDNA) damage.…”
Section: Oxidative Stress and Heart Diseasementioning
confidence: 99%
“…The complex distribution of NOX4 in the human fibroblasts evidenced by the confocal microscopy and immunocytochemical staining confirms the role of NOX4 in redox signalling in physiological and pathological conditions. Indeed, other authors have shown on A549 and human heart tissue that the alternative splicing of NOX4 brings to the presence of several NOX4 isoforms that differ in intracellular localization [18,19]. The study of splicing isoforms in human skin fibroblasts and keratinocytes as well as the expression of other two members of NADPH oxidase family releasing H 2 O 2 as the main product, DUOX1 and DUOX2, may be the purpose of further studies.…”
Section: Discussionmentioning
confidence: 98%